Negotiation Strategies and Constraints For Solo Female Travelers in Africa - Ngwira, Cecilia; Tse, Serene; Vongvisitsin, Thanakarn Bella (Cognizant, 2020)
This article presents constraints of solo female travelers to Africa based on their blogs reflecting their pretravel and during-travel constraints and the negotiations they adopted to energize their desire to travel to and within African countries. The study employs netnographic research methodology to understand complex social phenomena and assist researchers in developing themes from female travel bloggers’ experiences of solo travels to Africa. Using content analysis, the findings show that the constraints were mainly interpersonal, external, as well as intrapersonal. Family, friends, and the media presented solo women travelers with these constraints about Africa, which is perceived as a socially constructed “men’s space.” The study finds that despite these constraints, the bloggers felt adventurous and were satisfied with their African experience.